2019
DOI: 10.1186/s13561-019-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants of health insurance enrolment and dropout in urban district of Ghana: a cross-sectional study

Abstract: BackgroundEarlier studies have found significant associations between sociodemographic factors and enrolment in the National Health Insurance Scheme (NHIS) in Ghana. These studies were mainly household surveys in relatively rural areas with high incidence of poverty. To expand the scope of existing evidence, this paper examines policy design factors associated with enrolment and dropout of the scheme in an urban poor district using routine secondary data.MethodsThis study is a cross-sectional quantitative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
31
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 25 publications
(52 reference statements)
11
31
4
Order By: Relevance
“…Studies have shown that the economy would be sustainable after the guarantee of health service to all people (18,19). Poor enrollment and drop out in health insurance would significantly affect universal health coverage (20). Likewise, increasing government health expenditures would contribute to quality health service and also coverage (18,21,22).…”
Section: Situation Of Low-and Middle-income Countries and Healthmentioning
confidence: 99%
“…Studies have shown that the economy would be sustainable after the guarantee of health service to all people (18,19). Poor enrollment and drop out in health insurance would significantly affect universal health coverage (20). Likewise, increasing government health expenditures would contribute to quality health service and also coverage (18,21,22).…”
Section: Situation Of Low-and Middle-income Countries and Healthmentioning
confidence: 99%
“…In the Jirapa Municipality where the majority of the population is employed in subsistence agriculture and without reliable records of their income to qualify to contribute based on income, adverse selection and moral hazards were a common means of avoiding catastrophic expenditure. The residents would often enrol or renew the membership of household members who are most likely to fall sick [3] or renew their membership only when they were sick. To achieve equity in enrolment in the NHIS would require a review of the current at rate contributions levied on subscribers outside the formal sector.…”
Section: Discussionmentioning
confidence: 99%
“…This de nition however, is shrouded in ambiguity and therefore inadequate when the focus is on implementing a speci c policy on equity in health (20,21). For example, a variety of studies that explored perceptions of equity in the NHIS have often tended to focus generally on the socioeconomic or sociodemographic factors associated with enrolment and dropout (3,(24)(25)(26). Other studies have examined the subjects of equity and affordability in the NHIS and arrived at the conclusion that the at rate payment of premiums by those in the informal sector favoured richer people, although the burden of illness was greater for lower-income groups (27)(28)(29)(30)(31).…”
Section: Equity In Health Care: a Health Insurance Perspectivementioning
confidence: 99%
See 2 more Smart Citations